Role of the Financial Advisors to Ensure Effective Consumer Protection in the Financial Services Market - Waliszewski, Krzysztof (Journal of Finance and Financial Law, 2016)
The aim of the article is to present contemporary model of consumer protection, together with the assumptions of the model and identify the problems of the effectiveness of consumer protection. The answer to these problems can be a financial advisor profession, which according to the hypothesis of the article is the missing link between the consumer and the financial institution in ensuring the effectiveness.